Synthesis, crystal structure, and luminescent property of a Cu (II) coordination polymer based on benzene-1, 2-dicarboxylic acid and 1, 2-bis(pyridine-3-ylmethoxy)benzene. Issue 4 (3rd April 2017) - Ma, Feng-Ji; Gao, Yan-Ping; Guo, Meng-Jiao; Chen, Xiao-Tian; Liu, Xian-Yi; Liu, Lei-Lei
ABSTRACT: A new coordination polymer, [Cu(L)(bpmb)]n (I ) (L = benzene-1, 2-dicarboxylic acid, bpmb = 1, 2-bis(pyridine-3-ylmethoxy)benzene), has been hydrothermally synthesized and characterized by single X-ray diffraction, IR, element analysis, and thermal analysis. The compoundI shows a two-dimensional corrugated sheet with 4 4 6 2 topology. In addition, the luminescent property ofI is investigated.